2007
DOI: 10.4315/0362-028x-70.4.991
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Hazards Lurk in the Kitchens of Young Adults

Abstract: Food mishandling in home kitchens likely causes a significant amount of foodborne disease; however, little is known about the food safety hazards lurking in home kitchens. The purposes of this study were to audit the kitchens of young adults with education beyond high school to identify food safety problems and develop recommendations for education efforts. Researchers developed a criterion-referenced home kitchen observation instrument to assess compliance of home food storage and rotation practices (e.g., te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 13 publications
0
36
0
2
Order By: Relevance
“…When asked regarding these products, 57.9% of NoI respondents and 61.44% of YesI respondents answered they consume such products within the 3-days period. Not knowing the correct fridge temperature, shelving of foods in the fridge (Byrd-Bredbenner et al, 2007), and shelf life of opened dairy products may represent a food safety risk for those who did not answer correctly (NoI, 42.1%; YesI, 38.56%).…”
Section: Cold Food Storagementioning
confidence: 99%
See 1 more Smart Citation
“…When asked regarding these products, 57.9% of NoI respondents and 61.44% of YesI respondents answered they consume such products within the 3-days period. Not knowing the correct fridge temperature, shelving of foods in the fridge (Byrd-Bredbenner et al, 2007), and shelf life of opened dairy products may represent a food safety risk for those who did not answer correctly (NoI, 42.1%; YesI, 38.56%).…”
Section: Cold Food Storagementioning
confidence: 99%
“…As observational studies suggest, knowledge and self-reported behavior do not necessarily reflect the actual behavior (Behrens et al, 2010;Byrd-Bredbenner, Berning, Martin-Biggers, & Quick, 2013;Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;DeDonder et al, 2009;Dharod et al, 2007;Fein, Lando, Levy, Teisl, & Noblet, 2011;Hoelzl et al 2013;Kindall et al, 2004;Phang & Bruhn, 2011;Worsfold & Griffith, 1997). However, an insight into what consumers know and what they need to be educated about can be obtained by such reported behavior .…”
Section: Introductionmentioning
confidence: 99%
“…The observers found that the young adults performed approximately 50% of the recommended safe food-handling practices overall and only about 25% of the recommended hand washing procedures. In the online survey discussed previously, the results concerned with hand washing were interesting, because although young adults' knowledge of hand washing was high at 73%, just 36% were familiar with the most sanitary method to use for washing hands, and of that group, only 27% were observed practicing it (p < 0.0001; Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007b).…”
Section: Background On Food Safetymentioning
confidence: 90%
“…Compounding the cooling problem is that refrigerators often are packed so tightly with food that air circulation is restricted. Tight packing also increases food-to-food cross-contamination risk (Byrd-Bredbenner et al, 2007). Another aspect of -chill‖ is keeping perishable foods out of danger zone temperatures.…”
Section: Food Control Levels Of Microbial Contamination Of Domestic Rmentioning
confidence: 99%